REKONSTRUKSI KONSEP KAFĀ’AH SEBAGAI FONDASI KELUARGA SAKINAH: ANALISIS SOSIOLOGIS PANDANGAN KH AHMAD ZABIDI MARZUQI - Muhammad Adib Darmawan (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This article examines the concept of kafā’ah in Islamic marriage through an analysis of KH Ahmad Zabidi Marzuqi’s thought using a family sociology approach. The study aims to reconstruct the meaning of kafā’ah as a foundation for building a sakinah family and to assess its relevance within modern social contexts and Indonesian positive law. This research employs a qualitative approach in the form of a biographical study of a religious figure. Primary data were obtained through in-depth interviews with KH Ahmad Zabidi Marzuqi, while secondary data were collected from relevant literature on Islamic family law and family sociology. Data were analyzed interpretatively using Talcott Parsons’ structural-functional theory, particularly the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). The findings reveal that KH Ahmad Zabidi Marzuqi conceptualizes kafā’ah as a mechanism of functional balance within the family, emphasizing value compatibility, the husband’s moral leadership, and functional differentiation of spousal roles. However, critical analysis indicates that an excessive emphasis on hierarchical structures may limit relational flexibility in contemporary societies characterized by changing gender relations and increasing demands for marital partnership. Within the framework of Indonesian positive law, kafā’ah does not possess binding legal authority and functions primarily as an ethical and sociological consideration. Therefore, this article argues for the reconstruction of kafā’ah as a functional–participatory principle that is adaptive, equitable, and responsive to contemporary social dynamics.